La loa en las Indias: la obra de Antonio Marcos en las fiestas de coronación de Carlos IV en Cuenca de Perú (Estudios Humanísticos. Filología, 1997)
In this paper the recovery of a eulogistic piece -loa- composed by Antonio Marcos for the celebrations held in the city of Cuenca in Ecuador on the occasion of the coronation of King Charles IV of Spain is describe d. The work may not be of any great literary merit, but it does reflect the activity that was triggered by the great festivities organised by Spanish-American cities to celebrate events conncected with the monarchy. Such commemorative acts allowed the survival there of a minor literary genre which in Spain was in crisis.